Access to health services, food, and water during an active conflict: Evidence from Ethiopia - Abay, Kibrom A.; Abay, Mehari Hiluf; Berhane, Guush; Chamberlin, Jordan; Croke, Kevin; Tafere, Kibrom (2022)
Civil conflict began in Ethiopia in November 2020 and has reportedly caused major disrup tions in access to health services, food, and related critical services, in addition to the direct impacts of the conflict on health and well-being. However, the population-level impacts of the conflict have not yet been systematically quantified. We analyze high frequency phone surveys conducted by the World Bank, which included measures of access to basic ser vices, to estimate the impact of the first phase of the war (November 2020 to May 2021) on households in Tigray. After controlling for sample selection, a difference-in-differences approach is used to estimate causal effects of the conflict on population access to health services, food, and water and sanitation. Inverse probability weighting is used to adjust for sample attrition. The conflict has increased the share of respondents who report that they were unable to access needed health services by 35 percentage points (95% CI: 14–55 pp) and medicine by 8 pp (95% CI:2–15 pp). It has also increased the share of households unable to purchase staple foods by 26 pp (95% CI:7–45 pp). The share of households unable to access water did not increase, although the percentage able to purchase soap declined by 17 pp (95% CI: 1–32 pp). We document significant heterogeneity across popula tion groups, with disproportionate effects on the poor, on rural populations, on households with undernourished children, and those living in communities without health facilities. These significant disruptions in access to basic services likely underestimate the true bur den of conflict in the affected population, given that the conflict has continued beyond the survey period, and that worse-affected households may have higher rates of non-response. Documented spatial and household-level heterogeneity in the impact of the conflict may help guide rapid post-conflict responses.